Torsional deformation properties of SMA tapes and their application to bias-type reciprocating rotary driving actuator - Takeda, K.; Matsui, R.; Tobushi, H.; Pieczyska, E.A. (Archives of Mechanics, 2017)
In order to develop the reciprocating rotary driving actuator with a simple mechanism using shape memory alloy (SMA) tapes, the graphical method to design the actuator was proposed based on the torsional deformation properties of SMA tapes. The torsional deformation properties of the SME tape showing the shape memory effect (SME) and the SE tape showing superelasticity (SE) were obtained. The bias-type reciprocating rotary actuator was composed of the pretwisted SME tape and the flat SE tape in series. The design chart expressed by the relationship between torque and twisting angle of the SME tape and the SE tape was proposed. The rotational angle and torque, which vary depending on temperature, can be estimated based on the design chart. The rotational angle is controlled by adjusting the mounting angle of the SME tape and the heating temperature. The automatically opening and closing blind driven by sunlight was demonstrated. The blind was controlled by using the reciprocating rotary element composed of the SME tape and the SE tape. The behavior of the blind can be achieved based on the proposed design method of the reciprocating rotary driving element.